Exaggeration of Language-Specific Rhythms in English and French Children's Songs - Hannon, Erin E.; Lévêque, Yohana; Nave, Karli M.; Trehub, Sandra E. (Frontiers in Psychology, 2016)
The available evidence indicates that the music of a culture reflects the speech rhythm of the prevailing language. The nPVI (normalized pairwise variability index) is a measure of durational contrast between successive events that can be applied to vowels in speech and to notes in music. Music–language parallels may have implications for the acquisition of language and music, but it is unclear whether native-language rhythms are reflected in children’s songs. In general, children’s songs exhibit greater rhythmic regularity than adults’ songs, in line with their caregiving goals and frequent coordination with rhythmic movement. Accordingly, one might expect lower nPVI values (i.e., lower variability) for such songs regardless of culture. In addition to their caregiving goals, children’s songs may serve an intuitive didactic function by modelling culturally relevant content and structure for music and language. One might therefore expect pronounced rhythmic parallels between children’s songs and language of origin. To evaluate these predictions, we analyzed a corpus of 269 English and French songs from folk and children’s music anthologies. As in prior work, nPVI values were significantly higher for English than for French children’s songs. For folk songs (i.e., songs not for children), the difference in nPVI for English and French songs was small and in the expected direction but non-significant. We subsequently collected ratings from American and French monolingual and bilingual adults, who rated their familiarity with each song, how much they liked it, and whether or not they thought it was a children’s song. Listeners gave higher familiarity and liking ratings to songs from their own culture, and they gave higher familiarity and preference ratings to children’s songs than to other songs. Although higher child-directedness ratings were given to children’s than to folk songs, French listeners drove this effect, and their ratings were uniquely predicted by nPVI. Together, these findings suggest that language-based rhythmic structures are evident in children’s songs, and that listeners expect exaggerated language-based rhythms in children’s songs. The implications of these findings for enculturation processes and for the acquisition of music and language are discussed.